Low birth weight and its associated risk factors: Health facility-based case-control study - K. C., Anil; Basel, Prem Lal; Singh, Sarswoti (PLOS ONE, 2020)
Background Low birth weight is a preventable public health problem. It is an important determinant of child survival and development, as well as long-term consequences like the onset of non-communicable disease in the life course. A large number of mortality and morbidity can be prevented by addressing the factors associated with low birth weight. The main objective of this study was to identify associated risk factors of low birth weight. Methodology A health facility-based unmatched case-control study was carried out from July 2018 to March 2019 among the mothers who delivered in health facilities of Dang district of Nepal from 17th August to 16th November 2018. The total sample size for the study was 369; 123 cases and 246 controls. Cases and controls were randomly selected independent of the exposure status in the ratio of 1:2. Information regarding exposure status was assessed through interviews and medical records. Mothers who delivered outside Dang districts were excluded from the study. Ethical clearance was obtained from the Institutional Review Committee (IRC) of the Institute of Medicine, Tribhuvan University and written consent was taken from each participant after explaining the objectives of the study. Results Multivariate logistic regression found that having the kitchen in the same living house (AOR 2.7, CI: 1.5–4.8), iron intake less than 180 tablets (AOR 3.2, CI: 1.7–5.7), maternal weight gain during second and third trimester less than 6.53 kg (AOR 2.6, CI: 1.5–4.7), co-morbidity during pregnancy (AOR 2.4, CI: 1.3–4.5), preterm birth (AOR 2.9, CI: 1.4–6.1) were the risk factors associated with low birth weight. Conclusion Having the kitchen in the same living house, iron intake less than 180 tablets during pregnancy, maternal weight gain less than 6.53 kg during the second and third trimester, co-morbidity during pregnancy and preterm birth were the risk factors associated with low birth weight.